AIR DEHUMIDIFIER BASED ON PELTIER AND ARDUINO - Voloshin, V. S.; Azarkhov, O. Yu.; Sili, I. I. (Medical Informatics and Engineering, 2020)
Background. Global warming is having a significant impact and will continue to have an impact on rising global humidity. Although the majority of the Ukraine population has not yet experienced this problem significantly, there are all prerequisites to believe that in the near future we will have an annual increase in humidity in all cities and villages of our country, come with restrict access of the population and facilities to drinking water. The problem will be urgently present to the cities which are territorially located near the sea coast, such as for example Mariupol. Of course, the availability of water for consumption is extremely important because it is the main source of life on Earth. Despite all the water found in the earth's crust, only 2.5 % of the water is fresh water. Of this small part, 70 % is used in agriculture, 23 % in industry and 7 % for human consumption. Results. This paper presents the development of a prototype of a dehumidification system that has the primary purpose of reducing indoor air humidity, first of all, in health care facilities (by condensation). Other benefits include: technical water storage, low cost, small size, portability. The process of removing water from the air must be clearly monitored so that the relative humidity in the room remains greater than the minimum permissible level. In order to avoid harm to the health of people and patients, humidity should be at least 30 %, if less — a possible negative impact on human health could be. The dehumidifier uses a 36 cm2 aluminum plate about 0.5 mm thick, a Peltier thermoelectric element, an Arduino UNO board, jumper wires, TIP122 transistors and 1 kOhm resistors. The Peltier thermoelectric element is a small unit that uses condensing technology to operate as a heat pump. Its thickness is only a few millimeters, the shape is square, it is 4x40x40 mm, the element contains small cubes of Bi2Te3 (bismuth telluride) in its structure. After connecting and applying voltage (12V) to the Peltier element in 4 minutes, droplets of water began to form on the plate. For ease of maintenance and design, each side of the element was marked with the letters «X» (stands for «cooling side») and «G» (stand for «heating side»). To control the cooler and power supply, the Arduino PWM of the corresponding PIN output was used and a signaling algorithm was installed. Digital control is used to create a square wave, the signal switches between on and off mode. Conclusions. As part of the initial results, we tested and obtained the process of condensation of water droplets on an aluminum plate, and the process itself turned out to be continuous and controlled. An important element in the further development of a generic model of dehumidifier for use in healthcare facilities should be the implementation of system feedback, such as the use of an Arduino-enabled humidity sensor.